Olympic marketing - Ferrand, Alain, 1952- (Taylor and Francis, 2012)
The Olympic Games have become the definitive sports event, with an unparalleled global reach and a remarkably diverse constituency of stakeholders, from the IOC and International Federations to athletes, sponsors and fans. It has been estimated, for example, that 3.6 billion people (about half of the world population) watched at least one minute of the Beijing Games in 2008 on television. The driving force behind the rise of the modern Olympics has been the Olympic marketing programme, which has acted as a catalyst for cooperation between stakeholders and driven the promotion, financial security and stability of the Olympic movement. This book is the first to explain the principles of Olympic marketing and to demonstrate how they can be applied successfully in all other areas of sports marketing and management. The book outlines a strategic and operational framework based on three types of co-productive relationships (market, network and informal) and explains how this framework can guide professional marketing practice. Containing case studies, summaries, insight boxes and examples of best practice in every chapter, this book is important reading for all students and practitioners working in sports marketing, sports management or Olympic studies.